La fase administrativa de adopción en el código de la niñez y adolescencia vulnera el principio constitucional y legal de celeridad procesal - Campaña Carrillo, Luis Rodolfo (2014)
The Code of Children and Adolescents establishes as one of its Principles " The interests of the child " and is geared to meet the effective exercise of rights of children and adolescents . The same Act regulates the legal institution of adoption but within its regulations specifically in the Administrative Phase of Adoption does not establish any term or term for the implementation of this phase, which becomes too long and cumbersome process , which in some cases causes the prospective adoptive desist from doing so consequently harm to minors that could be adopted , denying them the opportunity for a stable home and integral development , contravening the principle of best interests of the child. This research work entitled " THE FASE OF ADMINISTRATIVE CODE ADOPTION IN CHILDHOOD AND ADOLESCENCE BREACH THE CONSTITUTIONAL AND LEGAL PRINCIPLE celerity Scan the lack of provision in the Code on Children and Adolescents A mandatory deadline for compliance with the administrative phase of adoption , beginning with conceptual analysis of the family, its historical background , its forms of association among those found to adoption legal institution that is approached from its Historical background , characteristics , effects, and especially early The legal rules governing the adoption especially its phase Management in response to the constitutional principle of best interests of the Child, so that through the theoretical framework with the corresponding field research has determined that: There is a loophole in the Code on Children and Adolescents about the lack of a deadline for compliance with the administrative process of adoption is contrary to the principle of the best interests of the child, and should be subject to the technical units Adoption and Committees Family Allowance who are responsible for carrying out the administrative phase of adoption , and that principle is oriented to satisfy the exercise of the rights of children , girls and teenagers so that administrative and judicial authorities should adjust their decisions and actions for compliance.